PENGARUH CURRENT RATIO DAN DEBT TO ASSET RATIO TERHADAP RETURN ON ASSET PADA PERUSAHAAN MAKANAN DAN MINUMAN YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2018 – 2022 - Guspita Sari, Marni; Hidayat, Arif (Journal of Research and Publication Innovation, 2024)
This study aims to find out whether there is an effect of Current Ratio and Debt to Asset Ratio on Return on Asset in Food and Beverage Companies listed on the Indonesia Stock Exchange for the period 2018-2022. The population in this study is the financial statements of Food and Beverage Companies listed on the Indonesia Stock Exchange for the period 2018-2022. The research samples used are Profit and Loss statements, Total Assets statements, Current Assets Statements, Current Debt Statements, and Total Corporate Debt Reports published on the Indonesia Stock Exchange for the 2018-2022 period. The analysis in this study uses the SPSS (Statistical package for social science) Software program Version 26. The research method used was Quantitative, while the analysis technique used multiple regression analysis, classical assumption test (normality test, multicollinity test, heterokedasticity test), determination coefficient test (R2) and hypothesis test (t test and f test). The results of the study on the Current Ratio (X1) variable showed that there was a negative influence on Return on Asset, seen from the t-test (partial test) which showed the t-count value < the ttable. The Debt to Asset Ratio (X2) variable shows that there is a negative influence, judging from the calculation < the table. The results simultaneously/together show that there is an influence between the Current Ratio and the Debt to Asset Ratio on Return on Asset as seen from the results of the F test (simultaneous test) which shows the Fcal > Table. The results of the determination test show that th eAdjusted R square value is 0,266 or 26,6%, which means that the influence of the Current Ratio and Debt to Asset Ratio on Return on Asset in Food and Beverage Companies listed on the Indonesia Stock Exchange for the 2018-2022 period is 26,6% and the remaining 83,4% is influenced by other variables outside this study